4-Quadrant Vector Control for Induction Motor with Self-Commutated Rectifier for Power Factor Improvement - Moreno Martínez, Rodolfo (2001)
The present work shows the simulation results of the study performed on a system that improves the factor power of a network and diminishes the harmonic distortion of the current consumed by AC drives, giving the network the additional capability of energy regeneration. In order to improve the energie quality of the system, a three phase voltage source inverter is used instead of the classical diode-based rectifier. The proposed AC drive consists of a three phase voltage source inverter that drives an induction motor using the direct field orientation control method. The DC terminals of the AC drive is connected to a second inverter, which in turn is connected to the AC network by means of a three phase reactor or transformer in order to reduce the distortion of the AC current utility by keeping the AC current in phase with the voltage utility and maintaining the voltage at the DC link constant.